2005
DOI: 10.1080/02841850500216269
|View full text |Cite
|
Sign up to set email alerts
|

Posterior cranial fossa crowdedness is related to age and sex: an magnetic resonance volumetric study

Abstract: Our study shows that PCF CI is associated with age and sex, and can therefore be used as a surrogate to assess hindbrain atrophy in a cross-sectional sample. Moreover, sex- and age-specific normal ranges may be needed to evaluate the PCF CI in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…During the past decades, the PCF morphometry has been widely explored in TN. Previous studies indicated that the PCF morphometry might be similar in healthy subjects and classic TN patients (18,28,29). In addition, a smaller PCF was merely characterized as TNs without NVC, so-called idiopathic TNs (18).…”
Section: Discussionmentioning
confidence: 99%
“…During the past decades, the PCF morphometry has been widely explored in TN. Previous studies indicated that the PCF morphometry might be similar in healthy subjects and classic TN patients (18,28,29). In addition, a smaller PCF was merely characterized as TNs without NVC, so-called idiopathic TNs (18).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the results presented here are not matched by age and morphology which has been shown to be altered with age. 19,23,27,28,43,50 However, this age effect predominately impacts older populations such that the effect is likely small for a study population younger than 50 years of age. Less than 10% of our CMI and control subjects were older than 50 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…28 Also, Hayakawa et al found no significant differences in the midsagittal area of the pons or the cerebellar vermis between the 21-40 year old group and 51-60 year old group. 17 In addition, PCF crowdedness was reported as negatively correlated with age (0.8% per decade) by Lirng et al 27 However, the effect of age on PCF crowdedness between the ages of 24 and 50 years is not easily discernible due to the large variance within a small study population. Thus, one should control for demographics in brain morphological group comparisons.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lirng et al 9 used manual delineation of the PCF in MR imaging followed by image intensity-based segmentation of brain tissue and CSF to assess the effect of age and sex on the PCF volume and crowdedness in healthy subjects. They found that overall, men had a larger PCF and hindbrain volume, whereas women demonstrated a higher degree of crowdedness, which may explain the higher frequency of CMI in women.…”
mentioning
confidence: 99%